THE EFFECT OF USING DIFFERENT LEVELS OF CINNAMON OIL AND GINGER OIL ON SOME QUALITY, PHYSICAL CHARACTERISTICS OF LOCAL GOOSE MEAT STORED BY FREEZING FOR DIFFERENT PERIOD (Journal of Pharmaceutical Negative Results, 2022)
This study was conducted on 10/12/2021 until 15/11/2021 in the Graduate Studies Laboratory of the College of Agriculture, Kirkuk University / Department of Animal Production. In order to study the effect of using medicinal plant oils on some physical characteristics of thigh and breast meat for local frozen almonds for different periods at a temperature of -18°C, the meat was minced separately from the thigh and the breast, and the meat was mixed and naturalized. Then it was divided into five treatments, the first treatment (1) was considered the control treatment, as it was not treated with any additives, while cinnamon oil was added at a concentration of (0.25 ml ̸ kg of meat) to the second treatment (T2), and cinnamon oil was added at a concentration of (0.5 ml ̸ kg of meat) ) to the third treatment (T3), adding ginger oil at a concentration (0.25 ml/kg of meat) to the fourth treatment (T4), and adding ginger oil at a concentration (0.5 ml̸ kg of meat) to the fifth treatment (T5). And three replicates for each of the thigh and chest for each period, and were stored by freezing at a temperature of (-18) ° C for periods of 1, 15 and 30 days until physical examinations were performed. The study reached the following results: The treatment of adding cinnamon oil and ginger oil recorded the lowest percentage of loss during thawing and loss during cooking, with an improvement in the ability of meat to carry water when stored in freezing . As for the interaction between treatments and the effect of storage period and treatment effect, we note that there are significant (P<0.05) differences in all study treatments compared with the control treatment. As for the effect of freezing storage periods, the results were: Increasing the storage period led to an increase in the percentage of loss during thawing and loss during cooking and a significant decrease in water carrying capacity.